Postdischarge Mortality after Geriatric Low-Level Falls: A Five-Year Analysis. Issue 8 (August 2018) - Gerrish, Ashley W.; Hamill, Mark E.; Love, Katie M.; Lollar, Daniel I.; Locklear, Tonja M.; Dhiman, Nitasha; Nussbaum, Michael S.; Collier, Bryan R.
Geriatric trauma patients with low-level falls often have multiple comorbidities and limited physiologic reserve. Our aim was to investigate postdischarge mortality in this population. We hypothesized that five-year mortality would be higher relative to other blunt mechanisms. The registry of our Level 1 trauma center was queried for patients evaluated between July 2008 and December 2012. Adult patients identified were matched with mortality data from 2008 to 2013 from the National Death Index. Low-level falls were identified by E Codes; other types of blunt trauma were based on registry classification. Patients with multiple admissions were excluded. Univariate analysis was performed using Fisher's exact and Wilcoxon tests. Kaplan-Meier curves were plotted to compare postdischarge mortality. Seven thousand nine hundred sixteen patients were evaluated, 35.1 per cent were females. Patients aged less than 65 years and penetrating trauma were excluded, yielding 1997 patients—63.7 per cent with low-level falls versus 36.3 per cent with other blunt traumas. Geriatric patients sustaining low-level falls were older, more likely female, had a higher inpatient mortality, and were less likely to return home at discharge. Injury severity score, hospital length of stay, and intensive care unit length of stay were similar. Survival analysis demonstrated increased postdischarge mortality in the low-level fall group with 25 per cent mortality at 120 days. Geriatric patients with other blunt trauma had a significantly lower postdischarge mortality. Geriatric patients injured in low-level falls have a higher inhospital mortality, are more likely to be functionally dependent on discharge, and have a high post-discharge mortality. Opportunities likely exist for injury prevention, consideration of palliative care, and postdischarge rehabilitation.